Pengaruh Electronic Word Of Mouth Melalui Aplikasi Sosial Media Terhadap Niat Pembelian Luxcrime Kosmetik Pada Generasi Z - Wulan Nur Azizah; Zakky Fahma Auliya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Along with the rapid expansion of social media utilization in Indonesia, the phenomenon of Electronic Word of Mouth (eWOM) is increasingly in the spotlight. eWOM refers to the process of distributing information through digital channels that allow consumers to share experiences, opinions, or suggestions related to products or services online. In this framework, eWOM has become one of the most powerful marketing strategies, especially in reaching the young consumer segment. This group, which is very intense in interacting on social media, tends to trust reviews or recommendations from friends, family, or influencers more than conventional advertising. To understand the impact of e-WOM, this study adopts an information adoption model that includes elements such as information quality, information credibility, information quantity, information usefulness, and information adoption itself. This study uses an information adoption model and involves 140 female respondents in Surakarta who are interested in Luxcrime Cosmetics products on Instagram. The results of the analysis show that eWOM has a positive impact on purchase intentions, with credibility, quantity, and information usefulness playing an important role in information adoption. These findings provide important insights for marketers to design more effective social media communication strategies, especially for Generation Z.